Ecosystem‐based management of Amazon fisheries and wetlands. Issue 1 (3rd October 2018) - Goulding, Michael; Venticinque, Eduardo; Ribeiro, Mauro L. de B.; Barthem, Ronaldo B.; Leite, Rosseval G.; Forsberg, Bruce; Petry, Paulo; Lopes da Silva‐Júnior, Urbano; Ferraz, Polliana Santos; Cañas, Carlos
Abstract: Infrastructure development and overfishing in the Amazon make it imperative to define adequate scales for the ecosystem‐based management of commercial fisheries and the wetlands on which they depend. We mapped fisheries and fish ecology data from Brazil, Peru, Bolivia and Colombia to an explicit GIS framework of river basins and mainstems. Migratory species account for more than 80% of the known maximum catches of commercial fisheries across the Amazon. Of these migratory species, we nominated six long‐distance migratory fish taxa as flagship species to define the two main commercial fishery regions. The migrations of at least one goliath catfish species define a large‐scale longitudinal link joining the Andes, Amazon Lowlands and Amazon River estuary. Migratory Characiforms demonstrate interbasin wetland connectivity between nutrient‐rich and nutrient‐poor rivers over at least 2 million km 2, or about one‐third of the Amazon Basin. We show that flooded forest area is the most important wetland variable explaining regional variations in migratory characiforme biomass as indicated by maximum annual fishery catches. The sustainable management of Amazon fisheries will require transnational cooperation and a paradigm shift from local community management alone to a more integrated approach that considers both rural and urban consumers and challenges, and the realistic life histories of migratory species.